EARLY DETECTION OF CURRENCY CRISIS IN INDONESIA BASED ON STOCK PRICE INDEX USING VOLATILITY MODEL AND MARKOV SWITCHING - Berlyana Ayu Prasasti; Sugiyanto Sugiyanto; Sri Subanti (International Conference on Economic Business and Social Science, 2023)
The currency crisis occurred in Indonesia from 1997 until 1998 and 2008. These crises had a negative impact, both in terms of the economy and social life. Therefore, a system is needed to detect currency crisis to create economic and currency stability. The crisis can be detected through economic indicators, such as stock price index. This study aims to determine the appropriate model and determine the results of the prediction of the currency crisis in Indonesia from November 2022 to October 2023 based on stock price index. The research started by forming  model, then the volatility model which is , and then formed a combination of volatility and markov switching model. This combined model is used to form a smoothed probability that can detect crisis. The results showed that  is a suitable model and from November 2022 to October 2023 it is predicted that there will be no currency crisis in Indonesia.